What are the characteristics and results of Tilt Tests in the elderly? - Farias, Ana Gabriela Ponte; Ponte Filho, Arnóbio Dias da; Holanda, Marcela Albuquerque de; Dantas, Arthur Holanda; Freitas, Aston Alves de; Paiva, Rodrigo Carvalho; Kubrusly, Marcela Sobreira; Gondim, Davi Sales; Vidal, Pedro Barbosa Duarte; Maia, Fernanda Pimentel Arraes; Pinho, Luís Gustavo Bastos; Farias, Ana Gardênia Liberato Ponte; et al. (JOURNAL OF CARDIAC ARRHYTHMIAS, 2024)
Introduction: The elderly have several causes of syncope or pre-syncope. The importance of the Tilt Test (TT) has been questioned in this population. However, dysautonomic causes are common in these age groups, having an impact on morbidity and mortality. Objective: Compare the results of the TT between the age groups of the elderly (>=60 years) and the non-elderly. Methods: Crosssectional study carried out between 2016-2021. We used the Mann-Whitney and Chi-square tests, with a p-value < 5% considered significant. The protocols used were Westminster or Italian. Results: We analyzed 2364 tilt tests, 61.7% female, aged 51.1 (31-71) years. Positivity was 32.6%, 37.2% with sensitization (p < 0.0001). In the elderly group (EG), there were 958 tests (40.5%) and 1381 (58.4%) in the non-elderly (NEG). EG positivity was 270 (28.0%), lower than NEG with 524 (37.43%) (p < 0.01). Positivity with sensitization in EG was 195 (20.35%) x 403(29.18%) in NEG (p<0.001). In EG, 50 patients (5.22%) had a dysautonomic response and in NEG, there were 10 (0.72%) (p < 0.001). Complications were 4.2% EG x 2.6% NEG ( p= 0.03). Conclusion: The TT in the elderly showed a lower incidence of positivity in the passive and sensitization phases compared to the non-elderly. Vasovagal causes were the most frequent causes in the elderly, had a higher incidence of dysautonomic responses, fewer prodromes and a higher rate of complications, however without severity.